(untitled) (Acta Scientiarum. Biological Sciences, 2024)
On the Brazilian coast, the commercialization of Anomalocardia flexuosa is based on fishing in natural banks, but its stocks have been declining. As an alternative to this limitation, laboratory production is promising for plans of repopulation and cultivation of A. flexuosa. Aiming to develop techniques for this purpose, the current study evaluated the influence of temperature and salinity on the rearing of A. flexuosa larvae. Two experiments were conducted: (1) the effect of different salinities (25, 30, and 35 g L- 1) on survival and growth in the larval stage of A. flexuosa, lasting seven days; and (2) the effect of temperature (22 and 26 ºC) on larval growth and survival, lasting ten days. In both experiments, the D larvae were stored in experimental units (2 L) with a density of 10 larvae mL-1. At salinities of 25 and 30 g L- 1 there were greater survival rates. When analyzing the final length and the daily growth rate, the higher values were observed at salinity of 25 g L- 1, 126.08 ± 1.45 µm and 8.33±0.20 µm day-1, respectively. Regarding temperature, 26 ºC showed better values both for survival (62.25 ± 3.48%) and larval development (210.19 ± 0.56 µm). Thus, to optimize productivity, it is recommended to maintain salinity between 25–30 g L- 1 and a temperature of 26 °C.